2017
DOI: 10.1177/1932296817699847
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sitagliptin With Closed-Loop Technology to Decrease Postprandial Blood Glucose in Type 1 Diabetes

Abstract: Sitagliptin may be considered as an adjunct therapy in a closed-loop setting. Larger studies are needed to determine the role of oral agents like sitagliptin to lower postprandial hyperglycemia with closed loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Other potential oral adjunctive medications include dipeptidyl peptidase‐4 inhibitors such as sitagliptin, which was recently shown to decrease BG after the first 2 meals in the setting of closed‐loop insulin delivery over 25 hours in 15 patients with no significant effect on glucagon levels . SGLT2 inhibitors belong to a new class of oral anti‐diabetic medications that act by increasing renal glucose excretion, and may potentially be combined with CLS to improve glucose control.…”
Section: Challenges and Technical Issuesmentioning
confidence: 99%
“…Other potential oral adjunctive medications include dipeptidyl peptidase‐4 inhibitors such as sitagliptin, which was recently shown to decrease BG after the first 2 meals in the setting of closed‐loop insulin delivery over 25 hours in 15 patients with no significant effect on glucagon levels . SGLT2 inhibitors belong to a new class of oral anti‐diabetic medications that act by increasing renal glucose excretion, and may potentially be combined with CLS to improve glucose control.…”
Section: Challenges and Technical Issuesmentioning
confidence: 99%
“…One study looked at the effects of sitagliptin on postprandial glucose levels in those with type 1 diabetes treated with a closed-loop system. In this small study, the authors found a statistically significant decrease in postprandial glucose when sitagliptin was added, and they commented that insulin delivery was lower in the sitagliptin group [ 64 ]. No adverse events were reported by the authors, and there was no significant difference in the rate of hypoglycaemia between groups.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…DPP-4 inhibitors decrease postprandial hyperglycemia not only in T2DM but also in T1D [133]. In HIV + patients with impaired glucose tolerance who are on combination antiretroviral therapy, sitagliptin favorably improved inflammation, chronic immune cell activation and reduced glucose area under the curve [134].…”
Section: Clinical Studiesmentioning
confidence: 99%